Inhibitory TIGIT signaling is dependent on T cell receptor activation. - Zammit,WH; Le,Maistre LJ; Elliot,TAE; Cain,SA; Humphries,MJ; Davis,DM; Worboys,JD (Cell Rep, 2026)
The immune checkpoint receptor T cell immunoreceptor with Ig and ITIM domains (TIGIT) can signal via cytoplasmic motifs to regulate T cell function. The signaling molecules that mediate inhibitory TIGIT signaling and its regulation in T cells remain poorly defined. Here, proximity proteomics is employed to define TIGIT-proximal proteins upon CD155 engagement, identifying several that are ligation-specific, including those involved in signaling (Grb2 and SOS1), cytoskeletal regulation (CD2AP and SdcBP), and endocytosis (IST1 and SNX3). Through crosslinking followed by immunoprecipitation, we show that TIGIT and CD2AP directly interact, representing a novel association. A TIGIT mutant (Y225A/Y231A) incapable of inhibitory signaling prevents recruitment of these proteins. Strikingly, T cell receptor (TCR) stimulation is essential for TIGIT to engage with these pathways. Mechanistically, phosphorylation of TIGIT requires both CD155 ligation and TCR activation, resulting in its signaling and internalization. TCR activation-dependent TIGIT signaling establishes a regulatory mechanism that limits checkpoint control to when functionally required.